Evaluasi Kebijakan Pencegahan Perkawinan Anak Melalui Program Strategi Nasional Pencegahan Perkawinan Anak (STRANAS PPA) - Vivi Tri Handayani; Muhammad Syaroni Rofii (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
The child marriage rate in Indonesia is still relatively high, the government through Presidential Regulation (Perpres) Number 18 of 2020 concerning the RPJMN is targeting a reduction in the marriage rate in Indonesia by 8.74% through the National Strategy for the Prevention of Child Marriage (Stranas PPA). evaluate the policy on preventing child marriage through the Stratnas PPA program to see the achievement of targets and the effectiveness of implementing the policy. This study uses a qualitative descriptive method of retrospective policy analysis with a formal evaluation approach according to William n Dunn. This research resulted in: (1) Nationally, the prevalence target for women aged 20-24 who were married before the age of 18 decreased from 10.35 in 2020 to 9.23 in 2021, but in 2020 it did not reach the target, where the prevalence in 2020 it was 10.19, but the achievement reached 10.35; (2) based on indicators of implementation of coordination, there has been good coordination between the relevant Ministries/Institutions in efforts to prevent child marriage, but there are still 5 M/I that have not filled out the National Strategy for PPA matrix; (3) based on an analysis of the program's evaluation criteria, the PPA policy through the National Strategy PPA program is considered effective in efforts to prevent child marriage.